Perspective view of allogeneic IgG tumor immunotherapy - Ying Liu; Yuanyi Huang; Hong-Wei Cui; YingYing Wang; ZhaoWu Ma; Ying Xiang; Hong-Yi Xin; Jun-Qing Liang; Hong-Wu Xin (Cancer Cell International, 2024)
Abstract Allogeneic tumors are eradicated by host immunity; however, it is unknown how it is initiated until the report in Nature by Yaron Carmi et al. in 2015. Currently, we know that allogeneic tumors are eradicated by allogeneic IgG via dendritic cells. AlloIgG combined with the dendritic cell stimuli tumor necrosis factor alpha and CD40L induced tumor eradication via the reported and our proposed potential signaling pathways. AlloIgG triggers systematic immune responses targeting multiple antigens, which is proposed to overcome current immunotherapy limitations. The promising perspectives of alloIgG immunotherapy would have advanced from mouse models to clinical trials; however, there are only 6 published articles thus far. Therefore, we hope this perspective view will provide an initiative to promote future discussion.